Analysis of Rotor-to-Stator Rub in a Large Steam Turbogenerator - Paolo Pennacchi; Andrea Vania (International Journal of Rotating Machinery)
Rotor-to-stator rub is a very common topic in rotor dynamics and several models have been proposed in the literature. Anyhow these models are often able to explain only the experimental dynamical behaviour of simple test rigs, which are deliberately reproducing a Jeffcott rotor. On the contrary case, histories related to real machines are seldom presented and analysed. The aim of this paper is to present an actual case history of a large turbogenerator unit that was subjected to partial arc rubs. The experimental results are shown and discussed along with the model-based diagnostic strategy employed to identify the fault severity and the location of the shaft cross-sections where the heaviest rubs occurred. Comparisons between experimental data and simulated vibrations caused by the identified fault are shown to validate the proposed methodology.